Effectiveness of the internet-based Unified Protocol transdiagnostic intervention for the treatment of depression, anxiety and related disorders in a primary care setting: a randomized controlled trial. - Richards, Derek; Timulak, Ladislav (My University, 2022)
Background: Research has shown that internet-based cognitive behavioural therapy (iCBT) can be a very promising solution to increase access to and the dissemination of evidence-based treatments to all of the population in need. However, iCBT is still underutilized in clinical contexts, such as primary care. In order to achieve the effective implementation of these protocols, more studies in ecological settings are needed. The Unified Protocol (UP) is a transdiagnostic CBT protocol for the treatment of emotional disorders, which includes depression, anxiety and related disorders, that has shown its efficacy across different contexts and populations. An internet-based UP (iUP) programme has recently been developed as an emerging internet-based treatment for emotional disorders. However, the internet-delivered version of the UP (iUP) has not yet been examined empirically. The current project seeks to analyse the effectiveness of the iUP as a treatment for depression, anxiety and related emotional disorders in a primary care public health setting. Methods: The current study will employ a parallel-group, randomized controlled trial design. Participants will be randomly assigned to (a) the internet-based Unified Protocol (iUP), or (b) enhanced waiting list control (eWLC). Randomization will follow a 2:1 allocation ratio, with sample size calculations suggesting a required sample of 120 (iUP=80; eWLC=40). The Mini-International Neuropsychiatric Interview (M.I.N.I.) will be used for assessing potential participants. The Overall Anxiety Severity and Impairment Scale (OASIS) and the Overall Depression Severity and Impairment Scale (ODSIS) as well as other standardized questionnaires will be used for assessments at baseline, 4 weeks, 8 weeks and 12 weeks from baseline and for the iUP condition during the follow-up. Discussion: Combining the advantages of a transdiagnostic treatment with an online delivery format may have the potential to significantly lower the burden of emotional disorders in public health primary care setting. Anxiety and depression, often comorbid, are the most prevalent psychological disorders in primary care. Because the iUP allows for the treatment of different disorders and comorbidity, this treatment could represent an adequate choice for patients that demand mental health care in a primary care setting.
PUBLISHED